Pengaruh Frekuensi Rapat Dewan Komisaris dan Karakteristik Dewan Komisaris terhadap NilaiPerusahaan di Sektor Properti dan Real Estate - Mirna Zahra Baco; Rahman Anshari; Muhammad Iqbal Pribadi (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to analyze the effect of the frequency of board of commissioner meetings and the size of the board of commissioners on company value in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2023. This study uses a quantitative approach, this study utilizes secondary data obtained from the company's annual report. Of the total 94 companies listed on the IDX, the purposive sampling method was used to filter data according to certain criteria, resulting in 307 sample observations. The analysis was carried out using multiple linear regression with the help of SPSS software. The results of the study indicate that the size of the board of commissioners has a positive and significant effect on company value. Conversely, the frequency of board of commissioner meetings does not have a significant effect. This finding suggests that the composition and number of members of the board of commissioners have a more dominant role in creating company value, compared to how often meetings are held